Space and location of cerebral microbleeds, cognitive decline, and dementia in the community - Ding, Jie; Sigurðsson, Sigurður; Jónsson, Pálmi V; Eiriksdottir, Gudny; Meirelles, Osorio; Kjartansson, Olafur; Lopez, Oscar L; van Buchem, Mark A; Gudnason, Vilmundur; Launer, Lenore J (Neurology, 2017)
To assess the association of the number and anatomic location of cerebral microbleeds (CMBs), visible indicators of microvascular damage on MRI, with incident cognitive disease in the general population of older people. In the longitudinal population-based Age, Gene/Environment Susceptibility (AGES)-Reykjavik Study, 2,602 participants 66 to 93 years of age and free of prevalent dementia underwent brain MRI and cognitive testing of verbal memory, processing speed, and executive function at baseline and a mean of 5.2 years later. Adjudicated incident dementia cases were diagnosed according to international guidelines. In the multiple linear regression models adjusted for demographic, genetic, cardiovascular risk, and other cerebrovascular MRI markers, the presence of CMBs located in deep or mixed (deep and lobar) areas was associated with a greater decline in all 3 cognitive domains. Mixed CMBs were the strongest correlate for decline in memory and speed. Compared to those with no CMBs, participants with ≥3 CMBs had a steeper decline in a composite measure of global cognitive function, memory, and speed. Among those with ≥3 deep or mixed CMBs, associations were strongest for memory; the association with speed was strongest in those having ≥3 strictly lobar CMBs. People with ≥3 CMBs, regardless of their locations, had a higher incidence of all-cause dementia and vascular dementia. Mixed or a higher load of CMBs, with some specificity for location, is associated with accelerated cognitive decline in older people. These findings suggest a role for hypertensive vasculopathy and the combined effect of hypertensive and cerebral amyloid angiopathy in the pathogenesis of cognitive deterioration.